Stereotactic body radiotherapy for centrally located inoperable early-stage NSCLC: EORTC 22113-08113 LungTech phase II trial results - Levy, Antonin; Adebahr, Sonja; Hurkmans, Coen; Ahmed, Merina; Ahmad, Shahreen; Guckenberger, Matthias; Geets, Xavier; Lievens, Yolande; Lambrecht, Maarten; Pourel, Nicolas; Lewitzki, Victor; Konopa, Krzysztof; et al. (Journal of thoracic oncology, 2024)
Introduction - The international phase II single-arm LungTech trial 22113-08113 of the European Organization for Research and Treatment of Cancer assessed the safety and efficacy of stereotactic body radiotherapy (SBRT) in patients with centrally located early-stage NSCLC. - Methods - Patients with inoperable non-metastatic central NSCLC (T1-T3 N0 M0, ≤7cm) were included. After prospective central imaging review and radiation therapy quality assurance for any eligible patient, SBRT (8 × 7.5 Gy) was delivered. The primary endpoint was freedom from local progression probability three years after the start of SBRT. - Results - The trial was closed early due to poor accrual related to repeated safety-related pauses in recruitment. Between August 2015 and December 2017, 39 patients from six European countries were included and 31 were treated per protocol and analyzed. Patients were mainly male (58%) with a median age of 75 years. Baseline comorbidities were mainly respiratory (68%) and cardiac (48%). Median tumor size was 2.6 cm (range 1.2-5.5) and most cancers were T1 (51.6%) or T2a (38.7%) N0 M0 and of squamous cell origin (48.4%). Six patients (19.4%) had an ultracentral tumor location. The median follow-up was 3.6 years. The rates of 3-year freedom from local progression and overall survival were 81.5% (90% confidence interval [CI]: 62.7%-91.4%) and 61.1% (90% CI: 44.1%-74.4%), respectively. Cumulative incidence rates of local, regional, and distant progression at three years were 6.7% (90% CI: 1.6%-17.1%), 3.3% (90% CI: 0.4%-12.4%), and 29.8% (90% CI: 16.8%-44.1%), respectively. SBRT-related acute adverse events and late adverse events ≥ G3 were reported in 6.5% (n = 2, including one G5 pneumonitis in a patient with prior interstitial lung disease) and 19.4% (n = 6, including one lethal hemoptysis after a lung biopsy in a patient receiving anticoagulants), respectively. - Conclusions - The LungTech trial suggests that SBRT with 8 × 7.5Gy for central lung tumors in inoperable patients is associated with acceptable local control rates. However, late severe adverse events may occur after completion of treatment. This SBRT regimen is a viable treatment option after a thorough risk-benefit discussion with patients. To minimize potentially fatal toxicity, careful management of dose constraints, and post-SBRT interventions is crucial.
Online verfügbar: 22. Mai 2024, Artikelversion: 4. September 2024
Gesehen am 30.10.2024